2013
DOI: 10.1126/scitranslmed.3005576
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mediated Bone Tissue Morphogenesis from Tunable Nanolayered Implant Coatings

Abstract: The functional success of a biomedical implant critically depends on its stable bonding with the host tissue. Aseptic implant loosening accounts for over half of all joint replacement failures. Various materials, including metals and plastic, confer mechanical integrity to the device, but often these materials are not suitable for direct integration with the host tissue, which leads to implant loosening and patient morbidity. We describe a self-assembled, osteogenic, polymer-based conformal coating that promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 40 publications
(46 reference statements)
1
91
0
2
Order By: Relevance
“…Wadagaki et al, for example, demonstrated that the synthetic molecule simvastatin could be incorporated into electrospun nanofi bers that were deposited into a scaffold and that the subsequent release of simvastatin enhanced the formation of bone in vivo [ 105 ]. Shah et al used a chitosan/poly aspartic acid LbL nanofi lm system to load the osteoinductive bone morphogenetic protein 2 (BMP2) and hydroxyapaptite onto durable implants made of PEEK or titanium [ 106 ]. The inclusion of a hydrolytically cleavable molecule in the fi lms enabled tuning the BMP2 release and the coatings promoted bone regeneration in vitro and in vivo.…”
Section: Drug Release and Stem Cell Differentiationmentioning
confidence: 98%
“…Wadagaki et al, for example, demonstrated that the synthetic molecule simvastatin could be incorporated into electrospun nanofi bers that were deposited into a scaffold and that the subsequent release of simvastatin enhanced the formation of bone in vivo [ 105 ]. Shah et al used a chitosan/poly aspartic acid LbL nanofi lm system to load the osteoinductive bone morphogenetic protein 2 (BMP2) and hydroxyapaptite onto durable implants made of PEEK or titanium [ 106 ]. The inclusion of a hydrolytically cleavable molecule in the fi lms enabled tuning the BMP2 release and the coatings promoted bone regeneration in vitro and in vivo.…”
Section: Drug Release and Stem Cell Differentiationmentioning
confidence: 98%
“…Importantly, PEM assembly uses mild, aqueous conditions that preserve the activity of fragile biologics. We have previously demonstrated the importance of controlling the release of biologics from multilayer films by introducing the therapeutic as a layer during the PEM assembly process (15). Lack of toxicity is critical for materials used in implantable devices, and the long-term host response to permanent implants continues to be a concern.…”
Section: Discussionmentioning
confidence: 99%
“…The coating consisted of a micrometer-scale polyelectrolyte multilayer (PEM) thin film composed of layers of BMP-2 and PDGF-BB growth factors and may be adapted to release nanograms of growth factor per square millimeter for extended and physiologically meaningful time periods for bone healing by endogenous progenitor cells. Our previous studies have demonstrated that we can easily apply the PEM coatings to any substrate of choice, which can be other orthopedic polymers such as polycaprolactone and polyether ether ketone, metals such as titanium, and calcium phosphates (14)(15)(16)(17). To demonstrate the efficacy of this approach, we chose to coat a well-studied biodegradable porous poly(lactic-co-glycolic) acid (PLGA) membrane with well-understood physicochemical properties.…”
Section: Significancementioning
confidence: 99%
“…In allen anderen Gruppen gab es eine hohe Variabilität in der Knochenbildung und die maximalen Level wurden nicht gehalten [96]. Beschichtungen mit eingebautem BMP können auch aus synthetischen Polymeren wie dem hydrolytisch abbaubaren Poly(ß-aminoester) bestehen, der BMP2 ebenfalls langsam freisetzt und eine Steigerung der Resistenz gegen Zugkräfte an der Knochen-Implantat-Grenzfläche zeigte [97]. Eine andere Möglich-keit sind natürlich vorkommende Polymeren wie Chitosan, wobei sich eine Beschichtung aus Chitosan/Silikat/BMP auf porösem Titan ebenfalls günstig auf die Knochenbildung im Kaninchenmodell auswirkte [98].…”
Section: Bone Morphogenetic Proteinsunclassified